Description of a new species of the genus Metaplax H. Milne Edwards, 1852 (Decapoda: Brachyura: Varunidae) from Vietnam - Hsu, Jhih-Wei; Shih, Hsi-Te; Ngo, Xuan Quang (Zootaxa, 2025)
Metaplax H. Milne Edwards, 1852, is a genus in the family Varunidae H. Milne Edwards, 1853, distributed across the Indo-West Pacific, with 10 described species. Among them, Metaplax crenulata (Gerstaecker, 1856) was previously thought to be present in both the Indian Ocean and the western Pacific (Vietnam). However, our study, based on morphological and molecular evidence, indicates that specimens from the Indian Ocean and Vietnam represent distinct species. Since the type locality of M. crenulata is unknown, we conducted comparative analyses of the syntypes alongside specimens from the Indian Ocean and Vietnam. Morphological examinations revealed that the syntypes closely resemble the Indian Ocean specimens, whereas the Vietnamese specimens exhibit clear morphological differences, particularly in the male suborbital cristae and the proportions of the ambulatory legs. Furthermore, cytochrome c oxidase subunit I (COI) sequence analysis showed a 5.8% genetic divergence between the two groups, further confirming that they represent separate species. Based on these findings, we describe the species from Vietnam as new.